Architectural Network as Dynastic Strategy in Fontainebleau's Galerie des Cerfs. (2021) - Narkin, Elisabeth
Abstract : Around 1604, Henri IV commissioned a cycle of mural maps depicting royal residences in Fontainebleau's newly constructed Galerie des Cerfs. The gallery was part of Henri IV's response to the dynastic disruption and civil war that had precipitated his ascendance and was designed to signal his authority over France as a unified realm. This article examines the Galerie des Cerfs in the context of contemporary cartography and architecture as an expression of continuity at a moment when the royal family's retreat to the Paris region threatened the political efficacy of the architectural network that had previously sustained the monarchy.